Treatment of Multiple Actinic Keratosis and Field of Cancerization with Topical Piroxicam 0.8% and Sunscreen 50+ in Organ Transplant Recipients: A Series of 10 Cases - Virginia Garofalo; Alessandra Ventura; Sara Mazzilli; Laura Diluvio; Luca Bianchi; Luca Toti; Giuseppe Tisone; Massimo Milani; Elena Campione (Karger Publishers, 2017)
Organ transplant recipient (OTR) subjects are at high risk of skin cancer such as squamous cell carcinoma and basal cell carcinoma. Actinic keratosis (AK) is considered the precursor of these non-melanoma skin cancers. Sun protection is mandatory in subjects with AK and this preventive strategy is very important in OTR. Treatment of the field of cancerization is also crucial to reduce the risk of recurrence of skin lesions in AK and non-melanoma skin cancer patients. Activation of cyclooxygenase 1 and 2 enzymes plays an important role in the pathogenesis of skin cancers. Topical application of cyclooxygenase inhibitors such as diclofenac and, more recently, piroxicam has shown to reduce AK lesions in immunocompetent subjects. A medical device containing piroxicam and SPF 50+ sunscreen filters (P+SS) has been demonstrated to be effective in reducing AK lesions and improving the field of cancerization. We report the effect of P+SS, applied for 16 weeks, in a case series of 10 OTR subjects with multiple AK lesions. P+SS treatment was associated with a relevant AK lesion reduction (>75%) in 7 patients (with a complete clearance in 3 subjects) with an improvement in the field of cancerization. This medical device could be considered a promising long-term curative and preventive treatment in OTR patients at high risk of non-melanoma skin cancers.